Habilidade competitiva de soja e milho com espécies daninhas poáceas - Wandscheer, Alana Cristina Dorneles (2012)
The competition between plants is a major interference of agricultural systems and account for significant reductions in crop yield. This study aimed to evaluate the competitive ability of soybean and corn in coexistence with weed species Eleusine indica, Sorghum sudanense and Chloris distichophylla. There were eight experiments in green-house, University of Passo Fundo - RS, in the growing season 2010/2011. The treatments consisted of combinations of crops 23and weeds, respectively (8:0, 6:2, 4:4, 2:6 and 0:8) that corresponded to the proportions of 100, 75, 50, 25 and 0%. The competitive analysis was accomplished through diagrams applied to replacement series experiment and indexes of competivity. The variables analyzed were root and shoot dry weight, total and height of the plants. There were also experiments of mixed weed species Eleusine indica and Sorghumsudanense and crops. In this case, remained four soybean or corn plants per pot, and varied the proportions of weeds. Evaluations were performed in the same manner as in separate experiments, however it is also carried to the analysis of total dry weight crops, by comparison of measurements obtained in different proportions of weeds. In isolated infestations was observed competitive superiority of corn in relation to S. sudanense and C. distichophylla and competitive ability equivalent to E. indica. Soybean showed superior competitive ability of the three weed species. When in mixed infestations with corn, E. indica was more competitive than S. sudanense. However, S. sudanense more intensely reduced total dry weight of maize compared to E. indica. In the presence of soybean, S. sudanense was more competitive than E. indica. The largest reductions in total dry weight of soybean were observed in the presence of equal proportions of both weed species